Physical, psychological, and sexual violence as risk factors for social phobia in a sample of Moroccan students - Mohjat Belaatar; Adil Najdi; Adnane Louajri; Adil El Ammouri; Bousgheiri Fadila; Meftaha Senhaji (Middle East Current Psychiatry)
Abstract Background Social phobia is one of the most widespread mental disorders among young people, especially students. It may be due to several factors, the most important of which is violence and its various subtypes. Aim The main objective of the study was to identify the subtypes of violence that might be considered risk factors for social phobia. Methods In this descriptive study, the participants were students at different institutions of Abdelmalek Essaâdi University in Morocco. In total, we interviewed 1191 students of which 1154 are aged between 18 and 28, 34 between 29 and 39, 2 students are 44, and only 1 is 64, using the M.I.N.I. questionnaire, along with a background questionnaire that contains questions about childhood information and risk factors such as exposure to violence. Results The prevalence of social phobia among the students in this study was 27% (321 students) of whom 138 students (44.7%) had experienced physical violence, 108 (42.5%) had experienced psychological violence, and only 52 (36.9%) had experienced sexual violence. Conclusions The Moroccan population, despite its diversity, customs, and education, remains similar to other populations in terms of mental health and mental disorders.